Designing printed circuit stators for brushless permanent magnet motors - Gambetta, D.; Ahfock, A. (IET electric power applications, 2009)
The progress in a number of areas of technology has made printed circuit motors a serious contender for many applications. The modern cost effective neodymium magnets have allowed compact motor designs. Multi-layer circuit board production techniques have made the production of printed circuit coils cheaper and easier. However, in spite of the growing importance of printed circuit brushless motors, there is a lack of analytical tools to assist with their design. Geometrical analysis has been used to allow the plotting of printed circuit tracks to be carried out more systematically. The track plotting procedures have been linked with the finite element method to predict rotational electromotive force (EMF) waveforms. The six prototype motors were built and they were used to experimentally validate the method of predicting EMF waveforms. A general design algorithm is presented based on the suggested track plotting procedure and the EMF prediction technique.